PENGARUH LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP MINAT BERWIRAUSAHA - Dewi Kusuma Wardani; Rupertus Wilian Brodus Jelati (Jurnal Ekonomi Sakti, 2022)
This study aims to determine the influence of the family environment and peers on the interest in entrepreneurship to examine the influence of the family environment on the interest in entrepreneurship and to examine the influence of peers on the interest in entrepreneurship. This type of research is quantitative research, namely empirical research in which the data is in the form of numbers or something that can be calculated. When viewed from the research objectives, this research includes causal associative research, namely research that aims to see the effect of one variable with other variables. The sample taken in this study were accounting students in the city of Yogyakarta who collected 60 people. Data analysis used multiple linear regression analysis. The results showed that the family environment had a positive effect on interest in entrepreneurship and peers had a positive effect on interest in entrepreneurship.